Unveiling the enigma of blind box impulse buying curiosity: the moderating role of price consciousness - Gong, Xiyun; Yee, Choy Leong; Lee, Shin Yiing; Mohammad Saif, Abu Naser; Liu, Meilian; Anonthi, Fariah (Elsevier, 2024)
This study explores the causes of curiosity-driven impulse buying in blind boxes using the Stimulus-Organism-Response (S-O-R) model and adaptation level theory. It examines how store environment and product factors contribute to customer curiosity, incorporating price consciousness into the overall framework. Insights from an online survey of 306 Chinese respondents indicate that environmental factors and specific product characteristics positively influence consumer curiosity, while price consciousness has a negative moderate effect. The findings also show that customer curiosity stimulates impulse buying behavior and mediates the relationship between store atmosphere, surprise, and perceived novelty. This study identifies both objective and subjective factors behind blind box impulse buying and offers relevant suggestions for governments and consumers on managing impulse buying.